FAKTOR-FAKTOR YANG MEMENGARUHI MINAT PENGGUNAAN SIA BERBASIS BANK DIGITAL PADA MAHASISWA AKUNTANSI GENERASI Z DI SURABAYA DENGAN PENGARUH SOSIAL SEBAGAI VARIABEL MEDIASI - Annisa Ayu Ramadhiani; Rika Puspita Sari (CV. Denasya Smart Publisher, 2025)
This study analyzes the influence of perceived ease of use, perceived usefulness, trust, and security on the intention to use digital bank-based accounting information systems, with social influence as a mediating variable. The research was conducted on 120 Generation Z accounting students from universities in Surabaya using purposive sampling. The results show that perceived ease of use and security significantly influence usage intention, while perceived usefulness and trust do not. Perceived ease of use and usefulness affect social influence, but trust and security do not. Social influence does not mediate the relationship between the independent variables and usage intention. The findings indicate that technical factors are more dominant than social factors in encouraging the intention to adopt digital bank-based accounting information systems. These insights contribute to both academia and the banking industry in developing strategies for financial technology adoption.